MEMBANGUN MANUSIA BERKARAKER RELIGIUS: STUDI ANAK-ANAK TERLANTAR - Humaidi Humaidi; Kirana Fatmawati (Institut PTIQ Jakarta, 2019)
The case of child neglect is one of the main problems that is a challenge for the Indonesian people. Many parents deliberately leave their children in public places or in hospitals. One of the reasons is because the economic, social, family, or child factors are born with disabilities. So the parents do not want to take care of the child. To overcome this problem, the Jakarta Sayap Ibu Foundation is not only available to accommodate, care for and nurture the children of the Foundation but also foster their character through religious activities and ethics education. With this coaching, they can be virtuous, polite, and responsible, and can be useful people. In carrying out coaching, the method used is through habituation, disciplinary methods and storytelling methods. Based on the results of research conducted shows that the Jakarta Wings Mother Foundation has succeeded in educating and building their character into humans with religious characters. Fostering children's character through religious values is considered more effective than without religious values. This research is a type of qualitative field research, using the method of description-inductive and philosophical-analysis. In collecting data, researchers used observation, documentation and interview techniques.